Innovation Strategies and Health System Guiding Principles to Address Equity and Sustainability in Responsible Innovation in Health; Comment on "What Health System Challenges Should Responsible Innovation in Health Address? Insights From an International Scoping Review" - Sandra C. Buttigieg (Kerman University of Medical Sciences, 2019)
The insights from an international scoping review provided by Lehoux et al challenge health policy-makers, entrepreneurs/innovators and users of healthcare, worldwide, to be aware of equity and sustainability challenges at system-level when appraising responsible innovation in health (RIH) - purposefully designed to better support health systems.The authors manage to extract no less than 1391 health system challenges with those mostly cited pertaining to service delivery, human resources, leadership and governance. Countries were classified according to the Human Development Index (HDI), while the authors decided not to classify according to the types of health systems justifying this on the basis that the articles reviewed studied a specific setting within a broader national or regional health system. The article presents highly powerful and discerning viewpoints, indeed providing numerous standpoints, yet in a comprehensive manner, thereby putting structure to a somewhat highly complex and multidimensional subject. This commentary brings forth several considerations that are perceived on reading this article. First, although innovation strategies are important for the dynamicity of health systems, one should discuss whether or not RIH can adequately address equity and sustainability on a global scale. Secondly, RIH across countries should also be debated in the context of the principles garnered by the type of health system, thereby identifying whether or not the prevailing political goals support equity and sustainability, and whether or not policy-makers are adequately supported to translate system-level demand signals into innovation development opportunities. As key messages, the commentary reiterates the emphasis made by the authors of the need for international policy-oriented fora as learning vehicles on RIH that also address system-level challenges, albeit the need to acknowledge cultural differences. In addition, the public has not only the right for transparency on how equity and sustainability challenges are addressed in innovation decisions, but also the responsibilities to contribute to overcome these challenges.